A Movement Manipulator to Introduce Temporary and Local Perturbations in Human Hopping - Schumacher, Christian; Grimmer, Martin; Scherf, Andrej; Zhao, Guoping; Seyfarth, Andre; et al. (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2018)
Perturbations are used to study and identify mechanisms of human motor control. This study introduces a concept for a movement manipulator prototype to explore human response and recovery strategies following temporary perturbations at the local joint level. We utilized a soft human-machine interface in combination with a tethered actuation unit to perturb the ankle joint during single cycles of continuous hopping. Preliminary tests were performed where an external plantarflexion torque was introduced during the second half of stance. The experiment included a single subject and was used to analyze the functionality of the hopping phase detection algorithm and the manipulator performance. In order to explore the human response hopping kinematics, kinetics and muscle activity of ankle joint muscles were measured. Despite only small perturbation torques (0.006±.002Nm/BW) and powers (0.026±.008W/BW), significant responses in the movement execution were evoked. During the perturbated hop, take-off ankle angle increased by 2.9°, while for the first recovery hop, peak ground reaction force and early plantarflexor activity increased. In response to the applied temporal and local ankle joint perturbations, our results suggest that (1) joint kinematics were compensated during flight, whereas (2) joint kinetics were changed during the following stance phase.
CRIS-Team Scopus Importer:2021-09-24